Oxidative metabolism may be associated with negative symptoms in schizophrenia - Mehmet Gunes; Abdurrahman Altindag; Mahmut Bulut; Suleyman Demir; Aslihan Okan Ibiloglu; Mehmet Cemal Kaya; Abdullah Atli; Nurten Aksoy (Psychiatry and Clinical Psychopharmacology, 2017)
Objective: In the present study, we aimed to examine the relationship between the oxidative metabolism with disease severity, sociodemographic, and clinical characteristics in the patients with schizophrenia. Methods: Seventy-one patients with schizophrenia and 76 healthy volunteers were included in the study. Plasma total antioxidant level (TAL) and total oxidant level (TOL) were analyzed, and oxidative stress index (OSI) was calculated. Results: There was a statistically significant increase in TOL and OSI and decrease in TAL in the patients with schizophrenia compared to the controls (p < .05). There were positive, mild, statistically significant correlations between TOL, OSI, and Positive and Negative Syndrome Scale-Total scores (p = .01, p = .01, respectively), Positive and Negative Syndrome Scale-Negative scores (p = .002, p = .001, respectively), Positive and Negative Syndrome Scale Global Psychopathology scores (p = .03, p = .03, respectively), and Clinical Global Impression-Severity Scale scores (p = .008, p = .009 respectively). OSI levels were significantly lower in the patients who were on treatment with atypical antipsychotics (AAP) compared to the patients who were on typical antipsychotics (TAP) and combined antipsychotic (CAP) agents (p = .032). Conclusions: Oxidative stress was higher in schizophrenia patients. The increased severity of negative symptoms was in line with the disruption in oxidative balance. Oxidative stress is quite lower in AAP users compared to the TAP and CAP users. One of the mechanisms underlying the fact that AAPs are more effective on negative symptoms than typical agents may be the positive effect on the oxidative stress.